Validation of EULAR primary Sjögren's syndrome disease activity (ESSDAI) and patient indexes (ESSPRI). Issue 5 (17th January 2014) - Seror, Raphaèle; Theander, Elke; Brun, Johan G; Ramos-Casals, Manel; Valim, Valeria; Dörner, Thomas; Bootsma, Hendrika; Tzioufas, Athanasios; Solans-Laqué, Roser; Mandl, Thomas; Gottenberg, Jacques-Eric; Hachulla, Eric; et al.
Abstract : Objectives: To validate the two recently developed disease activity indexes for assessment of primary Sjögren's syndrome (SS): the European League Against Rheumatism (EULAR) SS Patient Reported Index (ESSPRI) and the EULAR SS Disease Activity Index (ESSDAI). Methods: A prospective international 6-month duration validation study was conducted in 15 countries. At each visit, physicians completed ESSDAI, SS disease activity index (SSDAI), Sjögren's Systemic Clinical Activity Index (SCAI) and physician global assessment (PhGA); and patients completed ESSPRI, Sicca Symptoms Inventory (SSI), Profile of Fatigue and Discomfort (PROFAD) and patient global assessment (PGA). Psychometric properties (construct validity, responsiveness and reliability) were evaluated and compared between scores. Results: Of the 395 patients included, 145 (37%) and 251 (64%) had currently active or current or past systemic manifestations, respectively. EULAR scores had higher correlation with the gold standard than other scores (ESSDAI with PhGA: r=0.59; ESSRPI with PGA: r=0.70). Correlations between patient and systemic scores were very low (ranging from 0.07 to 0.29). All systemic scores had similar large responsiveness in improved patients. Responsiveness of patient scores was low but was significantly higher for ESSPRI compared with SSI and PROFAD. Reliability was very good for all scores. Conclusions: ESSDAI and ESSPRI had good construct validity. All scores were reliable. Systemic scores had a large sensitivity to change in patients whose disease activity improves. Patient scores had a small sensitivity to change, however, significantly better for ESSPRI. Systemic and patient scores poorly correlated, suggesting that they are 2 complementary components that should be both evaluated, but separately.